STUDENT ERRORS IN WRITING THE ENGLISH MATHEMATICAL OPERATION IN HIGHER EDUCATION - Anna Cesaria; Edwar Kemal; Wahyudi Rahmat (LLDIKTI Wilayah X, 2022)
English has been well-known as the world's international language. As a means of global communication, it should be actively mastered both orally and in writing. Writing is one of the skills that must be mastered by the students. It is related to the words, phrases, clauses and sentences. Then, if the meaning is unclear, people will misunderstand about the meaning of the sentences. The research investigated student errors in writing the English mathematical operations. The research is focused on the operation of addition, subtraction, multiplication and division. The research used qualitative approach using test and interview to collect the data. After conducting the research, it shows that there are some types of errors found such as incomplete materials error, technical errors, errors in understanding the previous material, and language misinterpretation. Meanwhile, student errors in the type of data misuse, theorems and definition of misuseand also unverified solutions are not found on the research.